Response to treatment with grapiprant as part of a standard multimodal regimen in young dogs with appendicular joint osteoarthritis associated pain - Enomoto, Masataka; Hash, Jonathan; Cole, Tracey; Porcel Sanchez, Maria D.; Thomson, Andrea; Perry, Erin; Aker, Savannah; Nakanishi-Hester, Aoi; Haupt, Emily; Opperman, Logan; Roe, Simon; Thompson, Nichola Archer; et al. (Frontiers in Veterinary Science, 2024)
IntroductionThe response to medical management of young dogs with osteoarthritis (OA) associated pain has not been evaluated. Using an open-label design, the effectiveness, over a 4-month period, of standardized management (grapiprant/fish oil/exercise) for treating OA pain in young dogs was evaluated.MethodsIncluded dogs were 9 months-4 years of age; ≥3.6 kg body weight; had ≥1 appendicular joint with radiographic OA and obvious joint pain; had a Liverpool Osteoarthritis in Dogs (LOAD) score of ≥5. The non-steroidal anti-inflammatory piprant (grapiprant) was given at the recommended dose daily, omega-3 fatty acid supplementation was initiated at 100 mg/kg and then increased to 200 mg/kg daily, and leash exercise was gradually increased to a target of 60 min daily. Client-reported outcome measures (CROMs) and force plate gait analysis were collected at baseline and monthly for 4 months. The index limb was defined as the most severely affected limb at baseline.ResultsForty-eight dogs were enrolled (mean ± SD age of 30.7 ± 10.7 months). Hips, elbows, and stifles were commonly affected. Medication and supplement compliance was excellent (≥95% of target administered), and treatments were well-tolerated. CROMs showed significant improvement over time and at each time point. Overall, peak vertical force (PVF) increased significantly (<0.001), and vertical impulse increased numerically. Increase in PVF from baseline was significant at all time points except 4-months.DiscussionThis study demonstrates a clinically meaningful benefit of a multimodal treatment regimen over a 4-month period for young dogs (<4 years old) with OA-pain. Future work should determine if early, effective treatment is of long-term benefit.